International Experience Strategic Analysis of Financing Small Innovative Enterprises - D. N. Gavrilina (Управленческое консультирование, 2022)
The article analyzes the international experience of financing small innovative enterprises. The internal environment analysis of the small innovative enterprises financing infrastructure was carried out in China, Israel, European countries and the USA. The study touched upon a number of instruments that finance innovative enterprises, such as state financial support, the venture industry, the alternative investment market (various types of crowdfunding). Based on the conducted strategic analysis, the strengths and weaknesses of the small innovative enterprises financing infrastructure in the analyzed countries were identified. The conducted study of international experience will allow in the future to more comprehensively approach the strategic priorities development of the small innovative enterprises financing infrastructure in Russia at the national and regional levels.